Performance-based seismic assessment of vulnerability of dam using time history analysis - Elmrabet Oumnia; Boubel Hasnae; Mehdi Echebba El; Rougui Mohamed; Mouhat Ouadia (MATEC Web of Conferences, 2018)
The current performance-based seismic assessment procedure can be computationally intensive as it requires many time history analyses (THA) each requiring time intensive post-processing of results. Time history analysis is a part of structural analysis and is the calculation of the response of a structure to any earthquake. It is one of the main processes of structural design in regions where earthquakes are prevalent. The objective of this study is to evaluate the seismic performance of embankment dam located on the Oued RHISS in the Province of AL HOCEIMA using the THA method. To monitor structural behavior, the seismic vulnerability of structure is evaluated under real earthquake records with considering the soil-structure-fluide interaction. In this study, a simple assistant program is developed for implementing earthquake analyses of structure with ANSYS, ground acceleration–time history data are used for seismic analysis and dynamic numerical simulations were conducted to study and identify the total response of the soil-structure system.